PENGEMBANGAN APLIKASI KALENDER BALI BERBASIS ANDROID - Yoga Yudisthira Sandra, I Made; Mahendra Darmawiguna, I Gede; Windu Antara Kesiman, Made (Universitas Pendidikan Ganesha, 2014)
Calendar is a system showing a period of time. Hindu in Bali has a special calendar which is different with other common one, because Hindu in Bali believes that there is a positive and negative meaning in every single date. Based on the problem this research aimed to (1) design the appicalion of Balinese calendar Android-based and (2) implement the design of Balinese calendar Android-based. This application was developed in android-based mobile phone by using System Development Life Cycle process. The model used in designing was Waterfall method and implemented in Java program by using Juno Eclipse editor. The result of this research is an application of Balinese calendar android-based. There are four menus in this epplication such as calendar, otonan, odalan and sms setting. Calendar is used to show the calendarand the information about the day.Otonan is used to find the previous otonan day and the next one. Odalan is used to find the specific odalan day. SMS setting is used to send the sms.